Effects of Yoga Relaxation on Anxiety Levels among Pregnant Women - Novelia, Shinta; Sitanggang, Tantri Wenny; Yulianti, Afnita (Nurse Media Journal of Nursing, 2018)
Background: Self-reported maternal mood symptoms during pregnancy have been related to poor birth outcomes, including low birth weight, increased risk of premature delivery, and pre-eclampsia among pregnant women. A non-pharmacological method is needed to overcome mood symptoms such as anxiety during pregnancy.Purpose: This study aimed to evaluate the effects of yoga relaxation on anxiety levels among pregnant women at the third trimester.Methods: This study employed a quasi-experimental research design and involved 30 pregnant women at the third trimester who were equally divided into two groups. The levels of anxiety were measured by using Hamilton Anxiety Rating Scale (HARS). Data were analysed using the independent t-test and the paired sample t-test.Results: The results showed that there was a significant difference in the anxiety levels before and after the intervention in the experimental group (t=7.56, p=0.005), and there was a significant difference in the anxiety levels after the intervention between the experimental and control group (t=-9.289, p=0.005).Conclusion: Yoga relaxation had an effect on reducing anxiety levels among pregnant women at the third trimester. It is expected that pregnant women use yoga relaxation to decrease anxiety.